Planear o parto normal - Cristiane Cavalcante Gomes Ferreira; Renata Marien Knupp Medeiros; Luanna de Arruda e Silva Dalprá; Áurea Christina de Paula Corrêa (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2019)
Consultar PDF